Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Consider a sequence $(x_n)_n$ in Hilbert space $H$ such that $\langle x_m,x_n\rangle=\delta_{mn}$ where $\delta_{mn}$ equals one if $m = n$ and $C$ otherwise. Prove that $(x_n)_n$ is a weakly convergent sequence.

share|improve this question
    
One could use Bessel's inequality. –  David Mitra Dec 9 '12 at 14:04
    
Bessel's inequality could be applied to an orthonormal sequence only. –  Takasima Senko Dec 9 '12 at 14:40
    
Oops, I misread that "$C$"... –  David Mitra Dec 9 '12 at 14:44
    
If the problem is correct, we necessarily have $C=0$, otherwise we have $\langle x_m,x_1\rangle =C$ for $m\geqslant 2$. –  Davide Giraudo Dec 9 '12 at 14:56
    
Could you explain this in detail? –  Takasima Senko Dec 9 '12 at 15:03

2 Answers 2

Let $F:=\overline{\operatorname{Span}\{x_n,n\geqslant 1\}}$: it's a closed subspace of $H$, so we have $H=F\oplus F^\perp$.

We know, as $\{x_n\}$ is bounded, that it has a weakly converging subsequence. What we have to prove is that the limit doesn't depend on the choice of the subsequence.

Let $u_0$ a weak limit of $\{x_{k'}\}$. We can write $u_0=u'_0+u''_0$, where $u'_0\in F$ and $u''_0\in F^\perp$.

Testing the definition of weak convergence $\langle x_{k'},v\rangle\to \langle u,v\rangle$ with $v=u''$, we get that $u''=0$, and for each $j$, $\langle u',x_j\rangle=C$.

This determines $u'$, because if $u_1$ and $u_2$ are weak limits of a subsequence of $\{x_n\}$, using the preceding argument we get that $\langle u_1'-u_2',x_j\rangle=C-C=0$ for all $j$, so $\langle u'_1-u'_2,w\rangle=0$ for all $w$ in the linear span of the $x_k$, and by density for all $w\in F$, and $u''_1-u''_2=0$.

share|improve this answer
    
I tried as your sketch but I have no result. Could you please give me some hints? –  Takasima Senko Dec 9 '12 at 15:35
    
If $C=0$ then we could use Bessel's inequality. But how can you prove that $C=0$? And I don't understand your last question. Would you please post your proof? –  Takasima Senko Dec 9 '12 at 16:07
1  
You have written $\langle x_m,x_1\rangle =C$ for $m\geq 2$ recently but I think this is the assumptions of the problem because we have $\langle x_m,x_n\rangle =C$ when $m\neq n$. Please let me know if I misconstrued your idea. –  Takasima Senko Dec 9 '12 at 16:25
    
I understand your point: the convergence is not necessarily to $0$. I will think more about the problem (at least, the beginning show that we can restrict ourselves to the closure of the span of the $x_j$). –  Davide Giraudo Dec 9 '12 at 16:29
    
@DonDon I've rewritten the argument, now I hope it's correct. –  Davide Giraudo Dec 9 '12 at 16:57

We have $y_n=\frac{1}{n}\sum\limits_{i=1}^{n}x_i$ converges to $y$ in $H$. Then $e_i=x_i-y$, $1\leq i\leq n$ is an orthonormal system. Hence, $(e_i)$, $1\leq i\leq n$ are linearly independent.

Let $F_n=\operatorname{Span}\{x_1,\ldots ,x_n\}$, it is a closed subspace of $H$. For all $x$ in $H$, $x=u_n+v_n$, $u_n\in F_n$, $v_n\in F_n^\perp$. Then $u_n=\sum\limits_{k=1}^{n}\lambda_ke_k$ and $\langle x,e_k\rangle=\lambda_k$. So $u_n=\sum\limits_{k=1}^{n}\langle x,e_k\rangle e_k$.

By Pythagorean Theorem, $||x||=||\sum\limits_{k=1}^{n}\langle x,e_k\rangle e_k+v_n||=\sum\limits_{k=1}^{n}|\langle x,e_k\rangle|^2+||v_n||^2$. Therefore, $\sum\limits_{k=1}^{n}|\langle x,e_k\rangle|^2\leq||x||$. In other words, the series $\sum\limits_{k=1}^{\infty}|\langle x,e_k\rangle|^2$ converges. So $\lim\limits_{n\to\infty}\langle x,e_k\rangle=0$. We can derive that $\lim\limits_{n\to\infty}\langle x,x_k\rangle=\lim\limits_{n\to\infty}\langle x,y\rangle$. Q.E.D

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.